Toward an understanding of intermediate- and short-range defects in ZnO single crystals. A combined experimental and theoretical study - Lima, R. C. [UNESP]; Macario, L. R.; Espinosa, J. W. M. [UNESP]; Longo, V. M.; Erlo, R.; Marana, N. L. [UNESP]; Sambrano, J. R. [UNESP]; dos Santos, M. L. [UNESP]; Moura, A. P.; Pizani, P. S.; Andres, J.; Longo, Elson [UNESP]; et al. (Amer Chemical Soc, 2008)
A joint use of experimental and theoretical techniques allows us to understand the key role of intermediate- and short-range defects in the structural and electronic properties of ZnO single crystals obtained by means of both conventional hydrothermal and microwave-hydrothermal synthesis methods. X-ray diffraction, Raman spectra, photoluminescence, scanning electronic and transmission electron microscopies were used to characterize the thermal properties, crystalline and optical features of the obtained nano and microwires ZnO structures. In addition, these properties were further investigated by means of two periodic models, crystalline and disordered ZnO wurtzite structure, and first principles calculations based on density functional theory at the B3LYP level. The theoretical results indicate that the key factor controlling the electronic behavior can be associated with a symmetry breaking process, creating localized electronic levels above the valence band.